Ways to Improve Regulation of Audit Activities in the Context of Global Change - SHULGA, S. (Naukovij Vìsnik Nacìonalʹnoï Akademìï Statistiki, Oblìku ta Auditu, 2019)
Regulation of audit in Ukraine has long been a subject to debate between various stakeholder groups, which is caused by reforms of auditing procedures in Ukraine. The article’s objective is to assess the sufficiency of this regulation, to highlight the role and significance of professional organizations of Ukrainian auditors in evaluation and continuing training of auditors, in the development of their interactions and collaboration, in order to enhance their professional competencies.  Problems of audit regulation in Ukraine are explored in the context of the European integration processes and global change. The authorities of professional organizations of auditors and accountants are analyzed in the context of the Law of Ukraine “On Audit of Financial Statements and Auditing”. The analysis of legally fixed authorities of these professional organizations shows their enhanced role and contribution in the professional training of auditors. Yet, large numbers of professional organizations of auditors and accountants in Ukraine, lack of well-established mechanism for the continuing professional training of auditors, a wide range of professional development programs produced by various professional organizations without proper control of their quality and relevance to the current requirements are factors that may trigger conflict situations related with various approaches to problem solutions. Therefore, government regulation and oversight of professional organizations of auditors and accountants cannot be effectively integrated without a clear algorithm of institutional interactions in the process of harmonization on the auditing market. In focus of the article is the need to develop regulatory support for their interactions aimed at the implementation of existing legislation in the field of auditing. It is proposed to create a coordination council on interactions and cooperation of professional auditor organizations of Ukraine, to avoid monopolism or unfair competition between professional organizations. In order to form the necessary prerequisites for its effective activities, it is proposed to develop the appropriate regulatory framework; an improved model for regulation of auditing in Ukraine is designed.